FOMO AND GEN Z INVESTMENT BEHAVIOR: A QUALITATIVE STUDY ON EMOTIONAL BIAS IN FINANCE - Faris Ramadhan; Etty Sri Wahyuni; Adnan Suhardis; Robin; Sumantri (CV. RADJA PUBLIKA, 2025)
This qualitative study investigates how Fear of Missing Out (FOMO) influences Generation Z investment behavior and emotional bias in financial decision-making processes. The research employed an interpretive phenomenological approach with in-depth semi-structured interviews conducted among Generation Z investors in Indonesia to understand the psychological mechanisms underlying FOMO-driven investment decisions. Systematic thematic analysis revealed three primary themes: FOMO as an emotional investment driver, social media influence creating information asymmetry, and financial literacy functioning as a complex moderating factor. The findings demonstrate that FOMO operates as a powerful emotional compulsion that systematically overrides rational decision-making processes, with social media exposure to peers' investment success serving as the most potent trigger for impulsive investment behavior. A significant